STRATEGI MEMOTIVASI PESERTA DIDIK PADA PEMBELAJARAN GEOGRAFI DI KELAS XI IPS SMAN 5 PONTIANAK - Gea Nuranisa; Sulistyarini Sulistyarini; Putri Tipa A (Universitas Tanjungpura, 2021)
AbstractThis study aims to analyze the teacher's strategy in providing learning motivationto students of class XI IPS in geography lessons at SMAN 5 Pontianak. Theresearch method used is descriptive in the form of qualitative research. Sources ofdata in this study were a geography teacher and four students of class XI IPS. Thedata collection technique used was observation, interview, and documentationtechniques. The results of the study show the following findings: (1) The way theteacher prepares and delivers learning, namely preparing learning tools andlearning media, then taking attendance and conditioning the class so that learningcan begin immediately. The form of strategy used by the geography teacher so thatstudents are motivated to learn is by giving an overview of geography learning thatis in accordance with everyday life and choosing the right learning method. (2)The teacher's obstacle in motivating students is two factors, namely, internalfactors which are factors of the students themselves, such as a lack of awarenessthat learning is important. Then external factors, namely factors from outside,students become not concentrated on learning when there is another class thatdoes not have a teacher. In addition, the characteristics of different students arealso an obstacle for teachers to motivate students.Keywords: Teacher Strategies, Student Motivation